The relationship between asymmetry and athletic performance: A critical review - Maloney, S. J. (The Journal of Strength and Conditioning Research, 2019)
Symmetry may be defined as the quality to demonstrate an exact correspondence of size, shape, and form when split along a given axis. Although it has been widely asserted that the bilateral asymmetries are detrimental to athletic performance, research does not wholly support such an association. Moreover, the research rarely seeks to distinguish between different types of bilateral asymmetry. Fluctuating asymmetries describe bilateral differences in anthropometric attributes, such as nostril width and ear size, and are thought to represent the developmental stability of an organism. There is evidence to suggest that fluctuating asymmetries may be related to impaired athletic performance, although contradictory findings have been reported. Sporting asymmetries is a term that may better describe bilateral differences in parameters, such as force output or jump height. These asymmetries are likely to be a function of limb dominance and magnified by long-standing participation within sport. Sporting asymmetries do not seem to carry a clear influence on athletic performance measures. Given the vast discrepancy in the methodologies used by different investigations, further research is warranted. Recent investigations have demonstrated that training interventions can reduce sporting asymmetries and improve performance. However, studies have not sought to determine whether the influence of sporting asymmetry is independent of improvements in neuromuscular parameters. It may be hypothesized that the deficient (weaker) limb has a greater potential for adaptation in comparison to the strong limb and may demonstrate greater responsiveness to training.